Accelerated lipoprotein uptake by transplantable hepatomas that express hepatic lipase - Charles Donner; Sungshin Choi; Michael Komaromy; Allen D. Cooper (Journal of Lipid Research, 1998)
To test the hypothesis that hepatic lipase plays a key role in lipoprotein removal in vivo, a novel system was used. Hepatoma cells (HTC 7288c) were transfected with a cDNA encoding hepatic lipase in culture and grown as solid tumors in vivo. In culture, transfected cells degraded chylomicron remnants and low density lipoprotein (LDL) somewhat more efficiently than untransfected cells. Tumors from the transplanted cells produced hepatic lipase localized to the surface of tumors from transfected cells but not tumors from non-transfected cells, grown in the same rat. The tumors from transfected cells removed, per gm of tissue, 34% (P < 0.001) more 125I-labeled LDL than tumors from non-transfected cells in the same animal. The uptake of chylomicron remnants (by tumors from transfected cells) was also modestly enhanced (15 ± 6%, P < 0.005). There were no differences in the uptake of 125I-labeled albumin or 125I-labeled asialoglycoprotein. Compared to the liver, the untransfected tumors took up 12%, and the transfected tumors took up about 18% as much LDL per gram of tissue. The uptake of chylomicron remnants compared to liver was far lower. Both types of tumors had about twice as much LDL receptor related protein as the liver. Wild-type tumors had the highest level of LDL receptor, twice hepatic lipase-secreting tumors, and six times that of the liver. Using the novel approach of transfecting transplantable tumor cells with hepatic lipase, the ability of hepatic lipase to facilitate the removal of apoB-containing lipoproteins was demonstrated. The liver still removes low density lipoprotein and especially chylomicron remnants more rapidly than the tumors, suggesting factors in addition to hepatic lipase and LDL receptor level play a major role in hepatic lipoprotein removal.—Donner, C., S. Choi, M. Komaromy, and A. D. Cooper. Accelerated lipoprotein uptake by transplantable hepatomas that express hepatic lipase.